2020
DOI: 10.3390/md19010012
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, COX-2 Inhibition and Anticancer Activity of Sclerotiorin Derivatives

Abstract: The latest research has indicated that anti-tumor agents with COX-2 inhibitory activity may benefit their anti-tumor efficiency. A series of sclerotiorin derivatives have been synthesized and screened for their cytotoxic activity against human lung cancer cells A549, breast cancer cells MDA-MB-435 using the MTT method. Among them, compounds 3, 7, 12, 13, 15, 17 showed good cytotoxic activity with IC50 values of 6.39, 9.20, 9.76, 7.75, 9.08, and 8.18 μM, respectively. In addition, all compounds were tested in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Furthermore, the reported antitumor properties of salicylamide-containing compounds [42] , [43] , [44] prompted the current study due to the targeted salicylamide derivative formed through conjugation of the carboxylic group of aspirin with the nitrogen atom of piperidinyl heterocycle. Recent reports describing the pathophysiological role of COX-1/2 inhibitors in cancer disease and the discovered COX-2 inhibitors as antitumor also supported the rational of the current study [45] , [46] .…”
Section: Introductionsupporting
confidence: 81%
“…Furthermore, the reported antitumor properties of salicylamide-containing compounds [42] , [43] , [44] prompted the current study due to the targeted salicylamide derivative formed through conjugation of the carboxylic group of aspirin with the nitrogen atom of piperidinyl heterocycle. Recent reports describing the pathophysiological role of COX-1/2 inhibitors in cancer disease and the discovered COX-2 inhibitors as antitumor also supported the rational of the current study [45] , [46] .…”
Section: Introductionsupporting
confidence: 81%
“…The results revealed that all of the synthesized Methoxyphenyl thiazolecarboxamide derivatives did not exhibit antiproliferative activity with IC 50 values higher than 40 µM concentration except compounds 2f and 2e, and this means that these compounds have no cytotoxic activities against the used cell lines at the effective dose. There is strong relationship between the COX enzyme and tumer overexprasion, the COX-2 enzyme is usually overexpressed in severl sorts of human cancers, and the biological studies consistently explained that COX-2 inhibitors compounds can inhibit the tumor progression and metastasis in several animal models of cancer [ 44 , 45 ]. However, compounds like 2f with COX inhibitory and anticancer activities could be a promising agents for both targets.…”
Section: Resultsmentioning
confidence: 99%
“…Because the crystal structure of glucosidase from Saccharomyces cerevisiae cannot be obtained, the α-glucosidase homology model (PDB:3AXH) provided by SWISSMODEL Repository was used, and the model quality was evaluated [ 29 ]. The α-glucosidase homology model (PDB:3AXH) with compounds 1 – 5 was performed on Autodock, as described previously [ 31 , 32 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%